2003
DOI: 10.1046/j.1365-294x.2003.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia infection complexity among insects in the tropical rice‐field community

Abstract: Wolbachia are a group of intracellular bacteria that cause reproductive alterations in their arthropod hosts. Widely discordant host and Wolbachia phylogenies indicate that horizontal transmission of these bacteria among species sometimes occurs. A likely means of horizontal transfer is through the feeding relations of organisms within communities. Feeding interactions among insects within the rice-field insect community have been well documented in the past. Here, we present the results of a polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 25 publications
2
88
0
1
Order By: Relevance
“…Typically, only one strain of Wolbachia is present in each species of delphacid planthopper (12,18,25). Here, we observe a variety of strains infecting different Perkinsiella populations.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Typically, only one strain of Wolbachia is present in each species of delphacid planthopper (12,18,25). Here, we observe a variety of strains infecting different Perkinsiella populations.…”
mentioning
confidence: 72%
“…The diversity of strains infecting these Perkinsiella species is much greater than the diversity observed for Wolbachia strains infecting other planthopper species (12,18,25). Bayesian phylogenetic analysis of the wsp gene indicates there are multiple groups of Wolbachia strains in Perkinsiella planthoppers (Fig.…”
mentioning
confidence: 93%
“…There are double infections of Wolbachia in many species (eg, Werren et al, 1995;Jeyaprakash and Hoy, 2000;Kittayapong et al, 2003). It has been shown that double-infected males are incompatible with singleinfected females in some insects such as D. simulans (Merçot et al, 1995;Rousset and Solignac, 1995), Aedes albopictus (Sinkins et al, 1995), and Nasonia vitripennis (Perrot-Minnot et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Of the eighteen populations examined eleven were infected, four with only one and seven with two Wolbachia strains. Double infections (at least two Wolbachia strains found in one host individual) are only recorded in some homopteran species, such as whitefly (Nirgianaki et al, 2003) and the zig-zag leafhopper (Kittayapong et al, 2003). This is the first report of a double infection in aphids.…”
Section: Distribution Of Wolbachia In S Miscanthimentioning
confidence: 91%
“…None of these species was infected with Wolbachia. Then Kittayapong et al (2003) investigated tropical rice-field community insects in Thailand. Forty-nine of 209 rice-field insect species were infected with Wolbachia.…”
Section: Introductionmentioning
confidence: 99%